2003
DOI: 10.3732/ajb.90.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Leaf biomechanics, morphology, and anatomy of the deciduous mesophyte Prunus serrulata (Rosaceae) and the evergreen sclerophyllous shrub Heteromeles arbutifolia (Rosaceae)

Abstract: Leaf tensile properties were compared between the mesic deciduous tree Prunus serrulata (var. "Kwanzan") and the xeric and sclerophyllous chaparral evergreen shrub Heteromeles arbutifolia (M. Roem). All values for biomechanical parameters for H. arbutifolia were significantly greater than those of P. serrulata. The fracture planes also differed between the two species with P. serrulata fracturing along the secondary veins, while H. arbutifolia most often fractured across the leaf irrespective of the vein or me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 26 publications
3
49
0
1
Order By: Relevance
“…make the cells more rigid. Bulk elastic modulus in three tropical evergreen species averaged 15 MPa, comparing to 10 MPa in three deciduous species (Sobrado 1986) and was 22 MPa in the evergreen Heteromeles arbutifolia compared with 17 MPa in the deciduous Prunus serrulata (Balsamo et al 2003). On dehydration, the rigid cells of evergreen leaves undergo smaller volume change for a similar amount of turgor drop compared to cells of deciduous leaves (Sobrado 1986;Salleo and Lo Gullo 1990;Salleo et al 1997).…”
Section: Xeromorphismmentioning
confidence: 90%
See 1 more Smart Citation
“…make the cells more rigid. Bulk elastic modulus in three tropical evergreen species averaged 15 MPa, comparing to 10 MPa in three deciduous species (Sobrado 1986) and was 22 MPa in the evergreen Heteromeles arbutifolia compared with 17 MPa in the deciduous Prunus serrulata (Balsamo et al 2003). On dehydration, the rigid cells of evergreen leaves undergo smaller volume change for a similar amount of turgor drop compared to cells of deciduous leaves (Sobrado 1986;Salleo and Lo Gullo 1990;Salleo et al 1997).…”
Section: Xeromorphismmentioning
confidence: 90%
“…Another category of sclerenchymatic tissue are various sclereids, developing as idioblasts throughout the mesophyll (Fahn and Cutler 1992;Jordan et al 2005Jordan et al , 2013 Many evergreen species, especially those from mesic habitats, lack the abundant sclerenchyma component and instead depend on a tough epidermis, subepidermal collenchyma (Fig. 1 E) and/or cuticular layer for structural reinforcement (Fig.1 C, Balsamo et al 2003). An investigation of mechanical properties of isolated foliar cuticles of 13 Australian evergreen species has shown that cuticle thickness was correlated with resistance to tearing and that tensile strength and modulus of elasticity were much higher than those of leaf laminas (Onoda et al 2012).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Adicionalmente, esta disposición de cilindros parenquimatosos del esponjoso ( fig. 6f) permite que el mesófilo resista la deformación mecánica que experimenta durante la transpiración (Balsamo et al, 2003), pues esta geometría es de las más resistentes y estables en la naturaleza.…”
Section: Caracteres Anatómicos Asociados Al Plegamiento Foliarunclassified
“…Studies on the mechanical properties of grass leaves have elucidated much useful information such as the relationship of leaf tensile strength and stem flexibility to livestock palatability (OReagain 1993), digestibility (De Sousa et al 1982), resistance to trampling (Sun and Liddle 1993), and more recently, drought tolerance (Balsamo et al 2003(Balsamo et al , 2005. Although over 40 years ago Kneebone (1960) suggested that the stage of leaf development had an important impact on leaf tensile properties, this has not, to our knowledge, been systematically investigated for species displaying a clear developmental sequence along the stem such as that exhibited by Zea mays (Lawson and Poethig 1995).…”
Section: Introductionmentioning
confidence: 99%
“…During plant development, these features are particularly relevant as the evolutionary goal shifts from survival to reproduction and the successful passing on of potentially favorable genes. All of these ancillary extant conditions can be addressed by the utilization of techniques that investigate the gross biomechanical properties of leaves, as mechanical stability during development, the optimization of water relations, and reduction in the incidence of herbivory may be influenced by architectural, anatomical, and chemical characteristics (Balsamo et al 2003(Balsamo et al , 2005 and play a central role in the ability of any individual plant to survive to adulthood and successfully reproduce.…”
Section: Introductionmentioning
confidence: 99%